UR_GERICHTE 00/01 12 vom 4. Oktober 2000 - UR Obergericht (2000)
Strafgesetzbuch. Art. 139 Ziff. 1 i.V.m. Art. 21 Abs. 1 StGB. | Strafgesetzbuch. Art. 139 Ziff. 1 i.V.m. Art. 21 Abs. 1 StGB. Versuchter